Perancangan Sistem Informasi Manajemen Berbasis Komputer Guna Meningkatkan Pelayanan Pada Bagian Apotik Di RSU Kepanjen-Malang - Annisa Kesy G, Nanang Dwi Irhandi (Jurnal Teknik Industri, 2000)
For this time, preparation of information technology be in the process of revolution or big change precisely. Such was the case with the Apotik of RSU Panggung Kepanjen - Malang, which acceptance recipe system and the information process of medicines for consumer or for own hospital side still not make ose of management information system which use computer yet, with the result that, make it difficult for several side to processing lot of data become an information.